Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.13057/biodiv/d230333
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of cellulase-producing thermophilic fungi isolated from Sungai Pinang hot spring, Riau Province, Indonesia

Abstract: Abstract. Saryono, Novianty R, Suraya N, Piska F, Devi S, Pratiwi NW, Ardhi A. 2022. Molecular identification of cellulase-producing thermophilic fungi isolated from Sungai Pinang hot spring, Riau Province, Indonesia. Biodiversitas 23: 1457-1465. Thermostable cellulolytic enzymes have become a subject of interest in industrial processes due to their ability to degrade cellulosic polysaccharides at elevated temperatures produced by microorganisms such as fungi and bacteria. In the present study, cellulase-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Results showed that the wastewater sample had a thorium content of 5.50 ppm, temperature of 26.3°C, and pH of 2.4, indicating the possibility of microbial growth, particularly fungi. Previous studies have shown that fungi can survive in various extreme conditions, such as hot springs, hypersaline environments, heavy metal/radionuclides contaminated sites, textile/ industrial wastewater, and others (Tkavc et al 2017;Sanjaya et al 2021;Ezeonuegbu et al 2022;Lira et al 2022;Saryono et al 2022;Wingfield et al 2023).…”
Section: Isolation and Identification Of Indigenous Fungi From Zircon...mentioning
confidence: 99%
“…Results showed that the wastewater sample had a thorium content of 5.50 ppm, temperature of 26.3°C, and pH of 2.4, indicating the possibility of microbial growth, particularly fungi. Previous studies have shown that fungi can survive in various extreme conditions, such as hot springs, hypersaline environments, heavy metal/radionuclides contaminated sites, textile/ industrial wastewater, and others (Tkavc et al 2017;Sanjaya et al 2021;Ezeonuegbu et al 2022;Lira et al 2022;Saryono et al 2022;Wingfield et al 2023).…”
Section: Isolation and Identification Of Indigenous Fungi From Zircon...mentioning
confidence: 99%
“…The mixture was vortexed and boiled for 15 min at 100 • C. Next, 1 mL of Nelson reagent was added, and the absorbance was measured at 520 nm. Concentrations of reducing sugars were determined based on a standard curve of xylose concentrations and following the methodology of [29].…”
Section: Assessment Of Reducing Sugarsmentioning
confidence: 99%